2007
DOI: 10.1101/gad.1547707
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome stability mediated by histone variants H3.3 and H2A.Z

Abstract: Nucleosomes containing the histone variant H3.3 tend to be clustered in vivo in the neighborhood of transcriptionally active genes and over regulatory elements. It has not been clear, however, whether H3.3-containing nucleosomes possess unique properties that would affect transcription. We report here that H3.3 nucleosomes isolated from vertebrates, regardless of whether they are partnered with H2A or H2A.Z, are unusually sensitive to salt-dependent disruption, losing H2A/H2B or H2A.Z/H2B dimers. Immunoprecipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
475
4
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 502 publications
(512 citation statements)
references
References 41 publications
29
475
4
4
Order By: Relevance
“…Furthermore, these three residues are thought to participate in the regulation of histone-histone interaction stability [25]. Indeed, H3.3 nucleosomes isolated from avian cells stably expressing tagged H3.3 are unusually sensitive to salt-dependent disruption, resulting in loss of their H2A/ H2B dimers [26]. Moreover, a recent study in HeLa cells expressing tagged H3.3 showed that splitting events of H3.3-H4 tetramers could be detected during DNA replication in vivo, a process that could not be observed for H3.1 [27].…”
Section: H33 Properties Compared With Its Canonical Counterpartsmentioning
confidence: 99%
“…Furthermore, these three residues are thought to participate in the regulation of histone-histone interaction stability [25]. Indeed, H3.3 nucleosomes isolated from avian cells stably expressing tagged H3.3 are unusually sensitive to salt-dependent disruption, resulting in loss of their H2A/ H2B dimers [26]. Moreover, a recent study in HeLa cells expressing tagged H3.3 showed that splitting events of H3.3-H4 tetramers could be detected during DNA replication in vivo, a process that could not be observed for H3.1 [27].…”
Section: H33 Properties Compared With Its Canonical Counterpartsmentioning
confidence: 99%
“…In addition to the core histones H2A/H2B/H3/H4, metazoan genomes encode histone variants ,such as H3.3, H2A.Z, and H2A.X (Figure 1), that in contrast to the canonical histones are subject to replication-independent expression and assembly (Woodcock, 2006), with strong effects on nucleosome stability and compaction (Jin and Felsenfeld, 2007). It is generally thought that RNA polymerase and the transcriptional activation and elongation complexes destabilize nucleosomes, promoting nucleosome remodeling, and variant histone incorporation, which then further potentiate or stabilize gene expression (Bintu et al, 2011;Sutcliffe et al, 2009).…”
Section: Histone Variantsmentioning
confidence: 99%
“…In addition to regulated nucleosome assembly and disassembly through the action of histone chaperones and chromatin remodelers, nucleosome stability is influenced by histone modifications, histone variants, DNA features encoded in cis, and competition with DNA-binding factors in trans . A complete picture of the mechanisms governing nucleosome stability is fundamental to understanding how gene expression is dynamically regulated.Nucleosome stability has been studied in vitro using sensitivity to enzymatic digestion or salt concentration (Bloom and Anderson 1978;Burton et al 1978;Li et al 1993;Polach and Widom 1995;Wu and Travers 2004;Jin and Felsenfeld 2007). Genome-wide adaptations of these methods have been used to identify nucleosome position and stability in vivo.…”
mentioning
confidence: 99%
“…Nucleosome stability has been studied in vitro using sensitivity to enzymatic digestion or salt concentration (Bloom and Anderson 1978;Burton et al 1978;Li et al 1993;Polach and Widom 1995;Wu and Travers 2004;Jin and Felsenfeld 2007). Genome-wide adaptations of these methods have been used to identify nucleosome position and stability in vivo.…”
mentioning
confidence: 99%